Distribution and trend in the thermal growing season in China during 1961–2015. (2nd November 2017) - Cui, Linli; Shi, Jun; Ma, Yue; Du, Huaqiang
Abstract: Based on daily mean temperature at 1863 meteorological stations in China, the trend in the thermal growing season was investigated and time-evolving probability distributions of temperature were examined. Results showed that during 1961–2015, the growing season was extended at rates of 1.5–5.0 days decade −1 in Northeast China, North China, Northwest China, and western and central parts of Southwest China. This change was ascribed to an earlier start of the growing season at rates of 1.5–3.0 days decade −1 in North China, the northern and western parts of Northeast China, and the northeastern part of Northwest China, and a later end at rates of 0.5–2.5 days decade −1 in Northwest China, the western and northern parts of Southwest China, and the northwest of North China. The earlier start of the growing season was in accordance with the rapid warming of lower portions of the spring temperature distribution in Northeast China, North China, and Northwest China. The later end of the growing season corresponded to rapid warming in the lower percentiles of autumn temperature distribution in Northwest China. The growing season is more sensitive to warming of lower percentiles of temperature distribution than other portions.